Revitalisasi Desain Motif Pelo Ati Rifa’iyah Berdasarkan Data Hasil Analisis Selera Generasi Milenial - Lesmana, Handi Hermawan; Sunarya, Yan Yan (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
Indonesian Batik was recognized by UNESCO on October 2, 2009, as an Intangible Cultural Heritage (ICH) during the UNESCO session in Abu Dhabi. This art form must, of course, be preserved to prevent it from disappearing. This research aims to revitalize the Pelo Ati motif of Rifa'iyah batik in Batang Regency by developing and renewing existing batik designs. The new batik designs are tailored to the target market of the millennial generation. This research uses the ATUMICS method, supported by questionnaire data. This method is used as part of the revitalization process to analyze and understand market conditions. This is crucial for preserving existing values. The research results are design recommendations that create new compositions for the batik motifs, targeting the millennial generation.